MARKETING MIX FACTOR AIRLINE PASSENGERS PERSPECTIVE TOWARD HIGH SPEED RAIL LINKED 3 AIRPORTS - aussawariyathipat, sompong; Thuratham, Pimchanok; Vichasorn, Wannapa; Triyakun, Tipyaporn; ThongKerd, Monsirada; Arnuparb, Songpol (Rajamangala University of Technology Tawan-ok Social Science Journal, 2021)
The purpose of this research were to study and compare Marketing Mix Factor Airline of Passengers Perspective used Service Airline to High Speed Rail Linked 3 Airports. The 402 questionnaires had been collected from Thai passengers who were both inbound and outbound passengers which were operating flights within Don Mueang International Airport, Suvarnabhumi Airport and U-Tapao International Airport (Rayong-Pattaya). And purposive random sampling, The Questionnaire used for data collection was a 5 level estimation questionnaire. The statistics used for data analysis were frequency, percentage, mean, standard deviation, t-Test and F-Test. The research findings were: 1. Thai passengers had opinion about Marketing Mix Factor Airline of Passengers Perspective used Service Airline to High Speed Rail Linked 3 Airports Overall and each aspect had the highest mean value at the highest level. 2) The comparison of difference Marketing Mix Factor Airline of Passengers Perspective used Service Airline to High Speed Rail Linked 3 Airports. 2.1) The passengers difference age, marital status, level of education, occupation, average income received per month, average frequency of using the airline service and the purpose of traveling had Mix Factor Airline of Passengers Perspective used Service Airline to High Speed Rail Linked 3 Airports was overall statically different significant at the 0.05. 2.2) The passengers difference gender, Airlines that has used the most services and travel nature had Mix Factor Airline of Passengers Perspective used Service Airline to High Speed Rail Linked 3 Airports was overall no the significant difference.